Motivasi Berprestasi Peserta Ekstrakulikuler Futsal di Kecamatan Cikarang Selatan Kabupaten Bekasi - Januari Alfredo; Citra Resita; Resty Gustiawati (Jurnal Literasi Olahraga, 2020)
The problem in this study is that in the implementation of extracurricular activities, many students are absent, often lazy, chatting on their own, and do not listen to the trainer's instructions during the training process. This study aims to determine how well the achievement motivation of class X and XI students in participating in extracurricular futsal activities in high school in Cikarang Selatan District, Bekasi Regency. This research is a quantitative descriptive study using a survey method. The population in this study were students who took part in extracurricular futsal activities at high school in Cikarang Selatan District, Bekasi Regency. The instrument in this study used an attitude scale questionnaire, while the sampling technique was purposive sampling. that the subjects of this study were 30 students of class X and XI who took part in extracurricular futsal activities in Cikarang Selatan District Bekasi Regency. The data analysis used in this research is descriptive quantitative analysis with percentages. The results of this study indicate the achievement motivation of students in class X and XI futsal sman extracurricular in Cikarang Selatan sub-district, Bekasi district, in detail there are very good categories, namely 25 students by 83.3, good categories as many as 3 students by 10%, enough categories as many as 2 students for 6.7%, in the category of less and very less amounted to 0 students (0.0